Rwanda Climate Services for Agriculture: Transforming Rwanda’s rural farming communities and national economy through improved climate risk management - Project Newsletter 2019 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The Rwanda Climate Services for Agriculture (RCSA) project made great strides in 2019 starting with the launch of two partnerships on strengthening agricultural climate services in Rwanda with the Department for International Development (DFID) of the UK Government and the International Fund for Agricultural Development (IFAD). The project also marked the culmination of trainings in Participatory Integrated Climate Services for Agriculture (PICSA), becoming the first country in the world to train all districts in climate services, with a special focus on the youth as the future farmers and agribusiness leaders.